2023
DOI: 10.1002/bimj.202100386
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian design for minimizing prediction uncertainty in bivariate spatial responses with applications to air quality monitoring

Abstract: Model‐based geostatistical design involves the selection of locations to collect data to minimize an expected loss function over a set of all possible locations. The loss function is specified to reflect the aim of data collection, which, for geostatistical studies, could be to minimize the prediction uncertainty at unobserved locations. In this paper, we propose a new approach to design such studies via a loss function derived through considering the entropy about the model predictions and the parameters of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…For instance, when dealing with observations that involve both continuous and binary data in a bivariate context, relying on a multivariate normal approximation becomes uncertain for estimating the covariance structure accurately. As such, further work is required to explore alternative methods such as Copula based models for mixed outcomes [34]. In studies where high-dimensional multivariate data are observed, it could be important to use certain Vine-Copulas [35].…”
Section: Future Workmentioning
confidence: 99%
“…For instance, when dealing with observations that involve both continuous and binary data in a bivariate context, relying on a multivariate normal approximation becomes uncertain for estimating the covariance structure accurately. As such, further work is required to explore alternative methods such as Copula based models for mixed outcomes [34]. In studies where high-dimensional multivariate data are observed, it could be important to use certain Vine-Copulas [35].…”
Section: Future Workmentioning
confidence: 99%
“…To reduce the uncertainty about responses as well as uncertainty about model parameters or predictions, Caselton and Zidek (1984), Guttorp et al (1993), Zidek et al (2000), and Fuentes et al (2007) developed the maximum entropy theory. In several studies, other aspects of the network design have been considered, including multivariate responses (Li and Zimmerman, 2015), a new entropy-based loss function (Senarathne et al, 2020), and an efficient algorithm for optimization (Leung et al, 2020). It should be noted that some of these studies implement distribution-free methods, e.g.…”
Section: Introductionmentioning
confidence: 99%